Power optimization and static performance investigation of an island-mode doubly-fed induction generator (DFIG) - Palizban, O.; Mekhilef, Saad (2011)
This paper presents a performance investigation of power optimization by using a Proportional-Integral (PI) controller in a doubly-fed induction generator (DFIG). A detailed, dynamic model of a DFIG based on variable speed systems is presented in the dq-synchronous reference frame. Along with different controller types, a PI controller is chosen. Moreover, besides active and reactive power control, constraints and power optimization are discussed. Matlab software was used for simulation.